High heat shielding flash spun sheet
By adding a hybrid material loaded with magnesium oxide to the spinning raw material, and using flash spinning and hot pressing processes to prepare flash-spun sheets, the problem of insufficient heat-shielding performance of flash-spun products was solved, and the heat-shielding performance was significantly improved and the application depth was expanded.
Patent Information
- Application Number
- CN202310866664.5
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2023-07-14
- Publication Date
- 2026-06-23
- Estimated Expiration
- 2043-07-14
AI Technical Summary
Existing technologies do not address the heat-shielding performance of flash evaporation products, and the market demand for flash evaporation products with good heat-shielding performance remains unmet.
By adding a magnesium oxide-loaded hybrid material to the spinning raw material, flash-spun sheets are prepared using flash spinning and hot pressing processes. The mass fraction of the magnesium oxide-loaded hybrid material in the spinning raw material is 2% to 4%, and the heat-shielding performance is improved through a specific preparation method.
It significantly improves the heat-shielding performance of spun sheets, expands their application scope, and reduces the heat-shielding rate attenuation rate under high temperature and high humidity conditions, while increasing the longitudinal tensile strength.
Abstract
Description
Technical Field
[0001] This invention belongs to the field of flash evaporation production technology, and particularly relates to a high heat-shielding flash-spun sheet. Background Technology
[0002] Flash spinning refers to a spinning method in which a polymer solution is extruded under high pressure above the boiling point of the solvent, causing the solvent to flash and the polymer to cool and solidify, forming fibers. It is also known as solution flash spinning. It requires that the polymer and solvent not decompose above the solvent's boiling point, and that the solvent easily evaporates. The extruded solution stream, when suddenly pressure is reduced, causes solvent flash evaporation, solidifying the polymer into fibers. The most prominent feature of flash spinning technology is phase separation. During the dissolution process, the polymer and solvent are stirred under high temperature and pressure to form a homogeneous solution; in a low-pressure chamber, the pressure is slightly reduced, causing a certain degree of phase separation, forming a two-phase solution, one phase rich in polymer and the other rich in solvent; finally, when the solution enters room temperature and pressure air through the spinneret, the solvent converts into vapor and rapidly separates from the polymer.
[0003] US Patent Publication No. US8048513 relates to flash-spun bundles of fibers having a surface area of less than 10 m² / g and a crushing value of at least 1 mm / g.
[0004] Chinese Patent Publication No. CN114622341A relates to a polyethylene nonwoven fabric and its application. The invention is characterized in that the raw material of the polyethylene nonwoven fabric is mainly polyethylene, and the first average flexural stiffness (DG) of the polyethylene nonwoven fabric is 28–240 mN•cm, with a DG / XG ratio of 1.03–3.0. For the same sample, the larger average flexural stiffness test value is defined as the first average flexural stiffness (DG), and the smaller test value is defined as the second average flexural stiffness (XG). The polyethylene nonwoven fabric of this application has certain flexural stiffness and good air permeability.
[0005] European Patent EP1264013B1 relates to a method for flash-spinning a web of polymer-formed filaments into a polymer-formed membrane and laying the web to form a nonwoven cotton wadding material, comprising the following steps: flash-spinning a spinning fluid, substantially composed of a polymer-formed synthetic fiber and a spinning agent, into a spinning unit maintained at a lower pressure under a pressure greater than the self-generated pressure of the spinning fluid to form a web of polymer-formed filaments; applying static charge to the web by passing the web through a corona discharge and laying the web onto a grounded surface to form a filament-fiber wadding suitable for consolidation into a sheet.
[0006] Chinese Patent Publication No. CN114687069A relates to a multifunctional polymer nonwoven fabric and its fabric, characterized in that the reduction rate of its elongation at break, ▲E, is 0.20 to 0.50; ▲E = 1 / E2; E1 is the elongation at break of the multifunctional polymer nonwoven fabric without aging test treatment; E2 is the elongation at break of the multifunctional polymer nonwoven fabric after aging test treatment; the value of E2 is less than 0.5. The process of this application is simple and has wide applications.
[0007] Chinese Patent Publication No. CN114687068A relates to an improved flash-evaporated nonwoven fabric. This invention addresses the problem of brightness decline in existing flash-evaporated nonwoven fabrics after a period of use by providing an improved flash-evaporated nonwoven fabric. The improved flash-evaporated nonwoven fabric has a D65 fluorescence brightness loss rate ▲F of 0.20–0.30; where ▲F = 1 F2 / F1; F1 is the D65 fluorescence brightness of the unaged nonwoven fabric; F2 is the D65 fluorescence brightness of the aged nonwoven fabric. The aging process conditions are: irradiance of 60±2 W / m² in the wavelength range of 300–400 nm, black mark temperature of 65±2℃, air temperature in the test chamber of 38±3℃, relative humidity of 50±10%, and drying time of 1440 hours. The flash-evaporated nonwoven fabric of this invention can maintain high brightness after a period of use.
[0008] European patent EP2264230A3 relates to a fiber nonwoven sheet with a longitudinal uniformity index of less than about 82 (g / m2) 1 / 2, an elongation at break of more than about 15%, and a tensile strength to basis weight ratio of more than about 0.78 N / cm / g / m2. The sheet contains a tufted membrane fibrillary material and can be prepared by a spin process.
[0009] Chinese Patent Publication No. CN114908478A relates to a lightweight flash-evaporated polymer nonwoven fabric with a wet tensile strength retention rate of 0.70-0.85, a front surface smoothness of 180-250 seconds, and a basis weight of 35-45 g / m2. This invention is prepared using a flash evaporation process with polyethylene as the raw material. The lightweight flash-evaporated polymer nonwoven fabric of this application possesses good toughness and softness, while also exhibiting a good wet tensile strength retention rate, which is beneficial for extending its service life.
[0010] Japanese Patent JP4565005 relates to a method for flash spinning a nonwoven fiber sheet from a polymer solution containing approximately 12% to approximately 33% by weight of filler particles. The filler is preferably insoluble in the polymer. The resulting tufted film-fiber sheet exhibits increased air permeability without sacrificing any liquid barrier properties.
[0011] Chinese Patent Publication No. CN114990712A relates to a flash-spun fabric and its applications. The fabric, after being soaked in deionized water at 40°C, exhibits a wet transverse tensile strength of 1600–1900 N / m and a wet longitudinal tensile strength of 2800–3100 N / m, with a dynamic friction coefficient of 0.1–0.25 and a basis weight of 35–45 g / m². This application is applicable to the medical protective field, various protective clothing, etc.
[0012] European Patent EP1213374 relates to an improved flash-spun filamentous membrane fibrillary sheet for fluid microfiltration and aseptic packaging. The above and other properties of the invention are achieved through a sheet suitable for liquid microfiltration, which has permeability resulting in a pressure drop of less than 4 psid at a flow rate of 10 gal / hr and an efficiency of filtering 99% of 1- to 2-micron-sized dust particles at a pressure differential of 30 psid. The invention also relates to a sheet suitable for aseptic packaging, having a Gurley Hill porosity of less than 15 seconds and a spore number reduction value of at least 2.5.
[0013] However, there is no existing research on how to adjust the heat-shielding performance of flash evaporation products, while the market demand for heat-shielding flash evaporation products is objectively real. Therefore, how to improve the heat-shielding performance of flash evaporation products to expand the application depth of flash evaporation materials has become a technical problem that urgently needs to be solved in this field. Summary of the Invention
[0014] The purpose of this invention is to address the above-mentioned problems by providing a high heat-shielding spun sheet.
[0015] To achieve the above objectives, the present invention adopts the following technical solutions:
[0016] A high heat-shielding spun sheet, wherein the raw material of the spun sheet includes polyethylene, and the thickness of the spun sheet is 0.1 mm to 0.5 mm;
[0017] The heat-blocking rate of spun yarn is 15%–30%;
[0018] The heat shading rate was tested according to the national standard GB / T 41560-2022.
[0019] The thickness of the spun sheet is 0.15 mm to 0.3 mm.
[0020] The basis weight of the spun flakes is greater than 30 g / m2.
[0021] The basis weight of the spun sheets is less than 120 g / m2.
[0022] The basis weight of the spun sheets is less than 100 g / m2.
[0023] The basis weight of the spun sheets is less than 90 g / m2.
[0024] The heat-blocking rate of spun yarn is 15% to 20%.
[0025] The heat-blocking rate of spun yarn is 20% to 25%.
[0026] The heat-blocking rate of spun yarn is 25%–30%.
[0027] A high heat-shielding spun sheet, wherein the heat-shielding rate attenuation ΔS of the spun sheet is 5% to 15%;
[0028] Where: △S = (S0 - S10) / S0 * 100%
[0029] S0 is the initial heat-blocking rate of the spun sheet;
[0030] S10 is the final heat-blocking efficiency of the spun sheet;
[0031] Test of heat shading rate:
[0032] (1) Place it at 25℃ and 65% relative humidity for 24 hours; then measure its shading index and record it as the initial shading index S0;
[0033] (2) Then expose it to a dry hot atmosphere at 90°C for 6 hours, and then cool it at 25°C and 65% relative humidity for 24 hours;
[0034] (3) Repeat step (2) and after nine more treatments, measure the heat shading rate of the treated sample according to the national standard GB / T41560-2022 and record it as S10.
[0035] The attenuation rate ΔS of the heat-blocking efficiency of the spun yarn is 5% to 10%.
[0036] The attenuation rate ΔS of the heat-blocking efficiency of the spun yarn is 10% to 15%.
[0037] A high heat-shielding flash-spun sheet with a longitudinal tensile strength (MTS) greater than 4.5 KN / m.
[0038] A high heat-shielding spun sheet with a Glyrene air permeability resistance of less than 35s. The Glyrene air permeability resistance is the time required for 100ml of gas to pass through, and is tested according to the national standard GB / T458-2008.
[0039] A high heat-shielding spun sheet whose raw material also includes a hybrid material loaded with magnesium oxide.
[0040] The mass fraction of the magnesium oxide-loaded hybrid material in the mixture of the magnesium oxide-loaded hybrid material and polyethylene is 2% to 4%.
[0041] The processing method for magnesium oxide-loaded hybrid materials includes the following technical steps:
[0042] (1) Silica particle surface treatment solution:
[0043] Silica nanoparticles were added to deionized water and ultrasonically dispersed to obtain a dispersion. Polyvinyl alcohol powder was then added to the dispersion while heating and stirring. The heating temperature was controlled at 75℃~100℃ for dissolution and dispersion. After the polyvinyl alcohol solution was dissolved, the reaction was carried out for 24 hours to 60 hours. Then, the undissolved polyvinyl alcohol was removed by filtration to obtain a coating solution, which yielded a silica particle surface treatment solution.
[0044] The mass ratio of silica nanoparticles to polyvinyl alcohol powder is 1:8 to 1:13.
[0045] (2) Magnesium-containing precursor dispersion
[0046] The silica particle surface treatment solution prepared in step (1) is then added to magnesium chloride aqueous solution to continue the first-stage reaction, and chelated with polyvinyl alcohol to load on the surface of silica nanoparticles. Then, the pH value of the mixed solution is slowly adjusted to 10.5-12 with alkali, and the second-stage reaction is continued under alkali conditions to obtain magnesium-containing precursor dispersion.
[0047] The first-order reaction time is 24 to 36 hours, and the reaction temperature is 55℃ to 75℃;
[0048] The alkali can be a 0.2 mol / L sodium hydroxide solution or a potassium hydroxide solution;
[0049] The second-order reaction is carried out under alkaline conditions, and the reaction time is 5 to 10 hours.
[0050] The internal silicon dioxide is etched, and at the same time, the internal magnesium ions generate magnesium hydroxide precipitate in the alkaline solution, so that etching and precipitation can be carried out simultaneously.
[0051] (3) Hybrid materials supported on magnesium oxide
[0052] Finally, the magnesium precursor dispersion from step (2) was separated by centrifugation, and the lower layer of precipitate was taken to obtain the magnesium precursor dispersion. The lower layer of magnesium precursor was calcined in an aerobic environment at 180℃~200℃ for 15 minutes~30 minutes, and then rapidly heated to 440℃~450℃ within 1~5 minutes for calcination in an anaerobic environment for 45 minutes~60 minutes. After natural cooling, the magnesium oxide-loaded hybrid material was obtained.
[0053] During the calcination process, aerobic calcination is carried out first. Because the polyvinyl alcohol structure undergoes aerobic pre-oxidation and carbonization at 180℃, and magnesium hydroxide is oxidized and decomposed to generate magnesium oxide, it is then transferred to high-temperature anaerobic carbonization to generate magnesium oxide with excellent emission function, which improves the heat shielding performance of the product and avoids the dispersion problem of conventional blending. Furthermore, magnesium oxide is generated on the surface of carbon materials, forming a relatively stable hybrid material doped with magnesium oxide.
[0054] A method for processing high heat-shielding flash-spun sheets mainly includes the following technical steps: dissolving the spinning raw material in a spinning solvent to obtain a spinning solution, then flash spinning the spinning solution, followed by hot pressing and winding to obtain flash-spun sheets.
[0055] The spinning raw material is a hybrid material of polyethylene and magnesium oxide; the mass fraction of the magnesium oxide-loaded hybrid material in the spinning raw material (a mixture of magnesium oxide-loaded hybrid material and polyethylene) is 2% to 4%.
[0056] The mass fraction of the spinning raw material in the spinning solution is 6% to 18%.
[0057] The temperature for flash spinning is 180℃~230℃.
[0058] The hot pressing temperature is 100℃~115℃.
[0059] The spinning solvents are aromatic hydrocarbons, aliphatic hydrocarbons, alicyclic hydrocarbons, unsaturated hydrocarbons, halogenated hydrocarbons, alcohols, esters, fluorocarbons, and their analogues. The main solvents are trichlorofluoromethane, dichloromethane, and 1,1-difluoroethane, in a mass ratio of 4:5:1.
[0060] This application also provides another technical solution:
[0061] A method for processing high heat-shielding polypropylene flash-spun sheets mainly includes the following technical steps: dissolving the spinning raw material in a spinning solvent to obtain a spinning solution, then flash spinning the spinning solution, followed by hot pressing and winding to obtain flash-spun sheets.
[0062] The spinning raw material is a hybrid material of polypropylene and magnesium oxide supported; the mass fraction of the magnesium oxide supported hybrid material in the spinning raw material (a mixture of magnesium oxide supported hybrid material and polypropylene) is 2% to 4%.
[0063] The mass fraction of the spinning raw material in the spinning solution is 6% to 18%.
[0064] The temperature for flash spinning is 180℃~230℃.
[0065] The hot pressing temperature is 100℃~115℃.
[0066] Compared with the prior art, the positive effects of the present invention are:
[0067] This invention provides a method for preparing a hybrid material loaded with magnesium oxide, and discovers that adding a certain amount of the above-mentioned hybrid material loaded with magnesium oxide to the spinning raw material can significantly improve the heat shielding performance of the obtained flash-spun sheet, thereby expanding the application depth of the flash-spun sheet. Detailed Implementation
[0068] The present invention will now be described in further detail with reference to specific embodiments.
[0069] Example 1
[0070] This embodiment provides a high heat-shielding flash-spun sheet and its processing method. The main technical steps include: dissolving the spinning raw material in a spinning solvent to obtain a spinning solution, then flash spinning the spinning solution, and then hot pressing and winding to obtain the flash-spun sheet.
[0071] The spinning raw material is a hybrid material of polyethylene and magnesium oxide; the mass fraction of the magnesium oxide-loaded hybrid material in the spinning raw material (a mixture of magnesium oxide-loaded hybrid material and polyethylene) is 2%.
[0072] The processing method for magnesium oxide-loaded hybrid materials includes the following technical steps:
[0073] (1) Silica particle surface treatment solution:
[0074] Silica nanoparticles were added to deionized water and ultrasonically dispersed to obtain a dispersion. Polyvinyl alcohol powder was then added to the dispersion while heating and stirring. The heating temperature was controlled at 75℃~100℃ for dissolution and dispersion. After the polyvinyl alcohol solution was dissolved, the reaction was carried out for 24 hours to 60 hours. Then, the undissolved polyvinyl alcohol was removed by filtration to obtain a coating solution, which yielded a silica particle surface treatment solution.
[0075] The mass ratio of silica nanoparticles to polyvinyl alcohol powder is 1:8;
[0076] (2) Magnesium-containing precursor dispersion
[0077] The silica particle surface treatment solution prepared in step (1) is then added to magnesium chloride aqueous solution to continue the first-stage reaction, and chelated with polyvinyl alcohol to load on the surface of silica nanoparticles. Then, the pH value of the mixed solution is slowly adjusted to 10.5-12 with alkali, and the second-stage reaction is continued under alkali conditions to obtain magnesium-containing precursor dispersion.
[0078] The first-order reaction time is 24 hours, and the reaction temperature is 55℃~75℃;
[0079] The alkali can be a 0.2 mol / L sodium hydroxide solution or a potassium hydroxide solution;
[0080] The second-order reaction was carried out under alkaline conditions for 5 hours.
[0081] The internal silicon dioxide is etched, and at the same time, the internal magnesium ions generate magnesium hydroxide precipitate in the alkaline solution, so that etching and precipitation can be carried out simultaneously.
[0082] (3) Hybrid materials supported on magnesium oxide
[0083] Finally, the magnesium precursor dispersion from step (2) was separated by centrifugation, and the lower layer of precipitate was taken to obtain the magnesium precursor dispersion. The lower layer of magnesium precursor was calcined in an aerobic environment at 180℃~200℃ for 15 minutes~30 minutes, and then rapidly heated to 440℃~450℃ within 1~5 minutes for calcination in an anaerobic environment for 45 minutes~60 minutes. After natural cooling, the magnesium oxide-loaded hybrid material was obtained.
[0084] The mass fraction of the spinning raw material in the spinning solution is 7%.
[0085] The temperature for flash spinning is 210℃.
[0086] The hot pressing temperature is 100℃.
[0087] The spinning solvent is trichlorofluoromethane, dichloromethane, and 1,1-difluoroethane, with a mass ratio of 4:5:1.
[0088] The test results for this embodiment are shown in Table 1.
[0089] Example 2
[0090] This embodiment provides a high heat-shielding flash-spun sheet and its processing method. The main technical steps include: dissolving the spinning raw material in a spinning solvent to obtain a spinning solution, then flash spinning the spinning solution, and then hot pressing and winding to obtain the flash-spun sheet.
[0091] The spinning raw material is a hybrid material of polyethylene and magnesium oxide; the mass fraction of the magnesium oxide-loaded hybrid material in the spinning raw material (a mixture of magnesium oxide-loaded hybrid material and polyethylene) is 3%.
[0092] The processing method for magnesium oxide-loaded hybrid materials includes the following technical steps:
[0093] (1) Silica particle surface treatment solution:
[0094] Silica nanoparticles were added to deionized water and ultrasonically dispersed to obtain a dispersion. Polyvinyl alcohol powder was then added to the dispersion while heating and stirring. The heating temperature was controlled at 75℃~100℃ for dissolution and dispersion. After the polyvinyl alcohol solution was dissolved, the reaction was carried out for 24 hours to 60 hours. Then, the undissolved polyvinyl alcohol was removed by filtration to obtain a coating solution, which yielded a silica particle surface treatment solution.
[0095] The mass ratio of silica nanoparticles to polyvinyl alcohol powder is 1:10;
[0096] (2) Magnesium-containing precursor dispersion
[0097] The silica particle surface treatment solution prepared in step (1) is then added to magnesium chloride aqueous solution to continue the first-stage reaction, and chelated with polyvinyl alcohol to load on the surface of silica nanoparticles. Then, the pH value of the mixed solution is slowly adjusted to 10.5-12 with alkali, and the second-stage reaction is continued under alkali conditions to obtain magnesium-containing precursor dispersion.
[0098] The first-order reaction time is 30 hours, and the reaction temperature is 55℃~75℃;
[0099] The alkali can be a 0.2 mol / L sodium hydroxide solution or a potassium hydroxide solution;
[0100] The second-order reaction was carried out under alkaline conditions for 7 hours.
[0101] The internal silicon dioxide is etched, and at the same time, the internal magnesium ions generate magnesium hydroxide precipitate in the alkaline solution, so that etching and precipitation can be carried out simultaneously.
[0102] (3) Hybrid materials supported on magnesium oxide
[0103] Finally, the magnesium precursor dispersion from step (2) was separated by centrifugation, and the lower layer of precipitate was taken to obtain the magnesium precursor dispersion. The lower layer of magnesium precursor was calcined in an aerobic environment at 180℃~200℃ for 15 minutes~30 minutes, and then rapidly heated to 440℃~450℃ within 1~5 minutes for calcination in an anaerobic environment for 45 minutes~60 minutes. After natural cooling, the magnesium oxide-loaded hybrid material was obtained.
[0104] The mass fraction of the spinning raw material in the spinning solution is 10%.
[0105] The temperature for flash spinning is 220℃.
[0106] The hot pressing temperature is 110℃.
[0107] The spinning solvent is trichlorofluoromethane, dichloromethane, and 1,1-difluoroethane, with a mass ratio of 4:5:1.
[0108] The test results for this embodiment are shown in Table 1.
[0109] Example 3
[0110] This embodiment provides a high heat-shielding flash-spun sheet and its processing method. The main technical steps include: dissolving the spinning raw material in a spinning solvent to obtain a spinning solution, then flash spinning the spinning solution, and then hot pressing and winding to obtain the flash-spun sheet.
[0111] The spinning raw material is a hybrid material of polyethylene and magnesium oxide; the mass fraction of the magnesium oxide-loaded hybrid material in the spinning raw material (a mixture of magnesium oxide-loaded hybrid material and polyethylene) is 4%.
[0112] The processing method for magnesium oxide-loaded hybrid materials includes the following technical steps:
[0113] (1) Silica particle surface treatment solution:
[0114] Silica nanoparticles were added to deionized water and ultrasonically dispersed to obtain a dispersion. Polyvinyl alcohol powder was then added to the dispersion while heating and stirring. The heating temperature was controlled at 75℃~100℃ for dissolution and dispersion. After the polyvinyl alcohol solution was dissolved, the reaction was carried out for 24 hours to 60 hours. Then, the undissolved polyvinyl alcohol was removed by filtration to obtain a coating solution, which yielded a silica particle surface treatment solution.
[0115] The mass ratio of silica nanoparticles to polyvinyl alcohol powder is 1:13;
[0116] (2) Magnesium-containing precursor dispersion
[0117] The silica particle surface treatment solution prepared in step (1) is then added to magnesium chloride aqueous solution to continue the first-stage reaction, and chelated with polyvinyl alcohol to load on the surface of silica nanoparticles. Then, the pH value of the mixed solution is slowly adjusted to 10.5-12 with alkali, and the second-stage reaction is continued under alkali conditions to obtain magnesium-containing precursor dispersion.
[0118] The first-order reaction time is 36 hours, and the reaction temperature is 55℃~75℃;
[0119] The alkali can be a 0.2 mol / L sodium hydroxide solution or a potassium hydroxide solution;
[0120] The second-order reaction was carried out under alkaline conditions for 10 hours.
[0121] The internal silicon dioxide is etched, and at the same time, the internal magnesium ions generate magnesium hydroxide precipitate in the alkaline solution, so that etching and precipitation can be carried out simultaneously.
[0122] (3) Hybrid materials supported on magnesium oxide
[0123] Finally, the magnesium precursor dispersion from step (2) was separated by centrifugation, and the lower layer of precipitate was taken to obtain the magnesium precursor dispersion. The lower layer of magnesium precursor was calcined in an aerobic environment at 180℃~200℃ for 15 minutes~30 minutes, and then rapidly heated to 440℃~450℃ within 1~5 minutes for calcination in an anaerobic environment for 45 minutes~60 minutes. After natural cooling, the magnesium oxide-loaded hybrid material was obtained.
[0124] The mass fraction of the spinning raw material in the spinning solution is 14%.
[0125] The temperature for flash spinning is 230℃.
[0126] The hot pressing temperature is 115℃.
[0127] The spinning solvent is trichlorofluoromethane, dichloromethane, and 1,1-difluoroethane, with a mass ratio of 4:5:1.
[0128] The test results for this embodiment are shown in Table 1.
[0129] Example 4
[0130] This embodiment provides a high heat-shielding flash-spun sheet and its processing method. The main technical steps include: dissolving the spinning raw material in a spinning solvent to obtain a spinning solution, then flash spinning the spinning solution, and then hot pressing and winding to obtain the flash-spun sheet.
[0131] The spinning raw material is a hybrid material of polypropylene and magnesium oxide supported; the mass fraction of the magnesium oxide supported hybrid material in the spinning raw material (a mixture of magnesium oxide supported hybrid material and polyethylene) is 2%.
[0132] The preparation method of the magnesium oxide-loaded hybrid material is the same as in Example 1.
[0133] The mass fraction of the spinning raw material in the spinning solution is 10%.
[0134] The temperature for flash spinning is 215℃.
[0135] The hot pressing temperature is 110℃.
[0136] The spinning solvent is trichlorofluoromethane, dichloromethane, and 1,1-difluoroethane, with a mass ratio of 4:5:1.
[0137] The test results for this embodiment are shown in Table 1.
[0138] Example 5
[0139] This embodiment provides a high heat-shielding flash-spun sheet and its processing method. The main technical steps include: dissolving the spinning raw material in a spinning solvent to obtain a spinning solution, then flash spinning the spinning solution, and then hot pressing and winding to obtain the flash-spun sheet.
[0140] The spinning raw material is a hybrid material of polypropylene and magnesium oxide; the mass fraction of the magnesium oxide-loaded hybrid material in the spinning raw material (a mixture of magnesium oxide-loaded hybrid material and polyethylene) is 3%.
[0141] The preparation method of the magnesium oxide-loaded hybrid material is the same as in Example 2.
[0142] The mass fraction of the spinning raw material in the spinning solution is 12%.
[0143] The temperature for flash spinning is 210℃.
[0144] The hot pressing temperature is 112℃.
[0145] The spinning solvent is trichlorofluoromethane, dichloromethane, and 1,1-difluoroethane, with a mass ratio of 4:5:1.
[0146] The test results for this embodiment are shown in Table 1.
[0147] Example 6
[0148] This embodiment provides a high heat-shielding flash-spun sheet and its processing method. The main technical steps include: dissolving the spinning raw material in a spinning solvent to obtain a spinning solution, then flash spinning the spinning solution, and then hot pressing and winding to obtain the flash-spun sheet.
[0149] The spinning raw material is a hybrid material of polypropylene and magnesium oxide supported; the mass fraction of the magnesium oxide supported hybrid material in the spinning raw material (a mixture of magnesium oxide supported hybrid material and polyethylene) is 4%.
[0150] The preparation method of the magnesium oxide-loaded hybrid material is the same as in Example 3.
[0151] The mass fraction of the spinning raw material in the spinning solution is 15%.
[0152] The temperature for flash spinning is 225℃.
[0153] The hot pressing temperature is 114℃.
[0154] The spinning solvent is trichlorofluoromethane, dichloromethane, and 1,1-difluoroethane, with a mass ratio of 4:5:1.
[0155] The test results for this embodiment are shown in Table 1.
[0156] Comparative Example 1
[0157] This comparative example provides a method for processing flash-spun sheets, the main technical steps of which are: dissolving the spinning raw material in a spinning solvent to obtain a spinning solution, then flash spinning the spinning solution, and then hot pressing and winding to obtain flash-spun sheets.
[0158] The spinning raw material is polyethylene;
[0159] The mass fraction of the spinning raw material in the spinning solution is 10%.
[0160] The temperature for flash spinning is 220℃.
[0161] The hot pressing temperature is 110℃.
[0162] The spinning solvent is trichlorofluoromethane, dichloromethane, and 1,1-difluoroethane, with a mass ratio of 4:5:1.
[0163] The test results for this comparative example are shown in Table 1.
[0164] Comparative Example 2
[0165] This comparative example provides a flash-spun sheet and its processing method, which mainly includes the following technical steps: dissolving the spinning raw material in a spinning solvent to obtain a spinning solution, then flash spinning the spinning solution, and then hot pressing and winding to obtain a flash-spun sheet.
[0166] The spinning raw material is a hybrid material of polyethylene and magnesium oxide; the mass fraction of the magnesium oxide-supported hybrid material in the spinning raw material (a mixture of magnesium oxide-supported hybrid material and polyethylene) is 0.5%.
[0167] The processing method for the magnesium oxide-loaded hybrid material is the same as in Example 2.
[0168] The mass fraction of the spinning raw material in the spinning solution is 10%.
[0169] The temperature for flash spinning is 220℃.
[0170] The hot pressing temperature is 110℃.
[0171] The spinning solvent is trichlorofluoromethane, dichloromethane, and 1,1-difluoroethane, with a mass ratio of 4:5:1.
[0172] The test results for this embodiment are shown in Table 1.
[0173] Comparative Example 3
[0174] This comparative example provides a flash-spun sheet and its processing method, which mainly includes the following technical steps: dissolving the spinning raw material in a spinning solvent to obtain a spinning solution, then flash spinning the spinning solution, and then hot pressing and winding to obtain a flash-spun sheet.
[0175] The spinning raw material is a hybrid material of polyethylene and magnesium oxide; the mass fraction of the magnesium oxide-loaded hybrid material in the spinning raw material (a mixture of magnesium oxide-loaded hybrid material and polyethylene) is 1%.
[0176] The processing method for the magnesium oxide-loaded hybrid material is the same as in Example 2.
[0177] The mass fraction of the spinning raw material in the spinning solution is 10%.
[0178] The temperature for flash spinning is 220℃.
[0179] The hot pressing temperature is 110℃.
[0180] The spinning solvent is trichlorofluoromethane, dichloromethane, and 1,1-difluoroethane, with a mass ratio of 4:5:1.
[0181] The test results for this embodiment are shown in Table 1.
[0182] Comparative Example 4
[0183] This comparative example provides a flash-spun sheet and its processing method, which mainly includes the following technical steps: dissolving the spinning raw material in a spinning solvent to obtain a spinning solution, then flash spinning the spinning solution, and then hot pressing and winding to obtain a flash-spun sheet.
[0184] The spinning raw material is a hybrid material of polyethylene and magnesium oxide; the mass fraction of the magnesium oxide-loaded hybrid material in the spinning raw material (a mixture of magnesium oxide-loaded hybrid material and polyethylene) is 5%.
[0185] The processing method for the magnesium oxide-loaded hybrid material is the same as in Example 2.
[0186] The mass fraction of the spinning raw material in the spinning solution is 10%.
[0187] The temperature for flash spinning is 220℃.
[0188] The hot pressing temperature is 110℃.
[0189] The spinning solvent is trichlorofluoromethane, dichloromethane, and 1,1-difluoroethane, with a mass ratio of 4:5:1.
[0190] The test results for this embodiment are shown in Table 1.
[0191] Comparative Example 5
[0192] This comparative example provides a flash-spun sheet and its processing method, which mainly includes the following technical steps: dissolving the spinning raw material in a spinning solvent to obtain a spinning solution, then flash spinning the spinning solution, and then hot pressing and winding to obtain a flash-spun sheet.
[0193] The spinning raw material is a hybrid material of polyethylene and magnesium oxide; the mass fraction of the magnesium oxide-loaded hybrid material in the spinning raw material (a mixture of magnesium oxide-loaded hybrid material and polyethylene) is 7%.
[0194] The processing method for the magnesium oxide-loaded hybrid material is the same as in Example 2.
[0195] The mass fraction of the spinning raw material in the spinning solution is 10%.
[0196] The temperature for flash spinning is 220℃.
[0197] The hot pressing temperature is 110℃.
[0198] The spinning solvent is trichlorofluoromethane, dichloromethane, and 1,1-difluoroethane, with a mass ratio of 4:5:1.
[0199] The test results for this embodiment are shown in Table 1.
[0200] Table 1 Performance test data of this application
[0201] S0 (%) △S(%) MTS (KN / m) Greil air resistance (s) Example 1 18 13 4.76 11 Example 2 25 10 5.79 20 Example 3 28 8 6.34 35 Example 4 20 14 6.16 25 Example 5 24 9 8.21 30 Example 6 29 7 10.51 34 Comparative Example 1 7.3 25.2 3.63 5 Comparative Example 2 10.5 19.3 4.24 10 Comparative Example 3 13.2 16.6 4.41 12 Comparative Example 4 29.1 8.4 5.89 65 Comparative Example 5 30.5 7.9 6.01 72
[0202] Results Analysis: Comparing the above data, it can be seen that after adding the hybrid material with magnesium oxide load prepared in this application, the resulting flash-spun sheets show significant improvements in heat shielding performance and heat shielding rate attenuation rate, achieving the expected purpose of this invention.
[0203] The specific embodiments described herein are merely illustrative of the spirit of the invention. Those skilled in the art to which this invention pertains may make various modifications or additions to the described specific embodiments or use similar methods to substitute them, without departing from the spirit of the invention or exceeding the scope defined by the appended claims.
Claims
1. A high heat-shielding spun sheet, characterized in that, The raw material for the spun sheets includes polyethylene, and the thickness of the spun sheets is 0.1 mm to 0.5 mm. The heat-blocking rate of spun yarn is 15%–30%; The attenuation rate ΔS of the heat-blocking efficiency of spun yarn is 5% to 15%; Where: △S = (S0 - S 10 ) / S0*100%; S0 is the initial heat-blocking rate of the spun sheet; S 10 The final heat shielding efficiency of the spun sheet; Test of heat shading rate: (1) Place it at 25℃ and 65% relative humidity for 24 hours; then measure its shading index and record it as the initial shading index S0; (2) Then expose it to a dry hot atmosphere at 90°C for 6 hours, and then cool it at 25°C and 65% relative humidity for 24 hours; (3) Repeat step (2) and after nine more treatments, measure the heat-shielding rate of the treated sample according to the national standard GB / T 41560-2022, and record it as S. 10 ; The raw materials for the flash-spun sheets also include a hybrid material loaded with magnesium oxide, which is prepared through the following steps: Step 1: Add silica nanoparticles to deionized water and ultrasonically disperse to obtain a dispersion. Then add polyvinyl alcohol powder to the dispersion and control the heating temperature to 75℃~100℃ for dissolution and dispersion. After the polyvinyl alcohol solution is dissolved, react for 24 hours to 60 hours. Then remove the undissolved polyvinyl alcohol by filtration to obtain a coating solution, which is a silica particle surface treatment solution. Step 2: Add the silica particle surface treatment solution prepared in Step 1 to the magnesium chloride aqueous solution to continue the first-stage reaction, and perform a chelation reaction with polyvinyl alcohol to load it on the surface of silica nanoparticles. Then, slowly adjust the pH of the mixed solution to 10.5-12 with alkali, and continue the second-stage reaction under alkaline conditions to obtain a magnesium-containing precursor dispersion. Step 3: The magnesium-containing precursor dispersion from Step 2 is separated by centrifugation, and the lower layer of precipitate is taken to obtain the magnesium-containing precursor dispersion. The lower layer of magnesium-containing precursor is calcined in an aerobic environment at 180℃~200℃ for 15 minutes~30 minutes, and then rapidly heated to 440℃~450℃ within 1~5 minutes for anaerobic calcination for 45 minutes~60 minutes. After natural cooling, the magnesium oxide-loaded hybrid material is obtained.
2. The high heat-shielding spun sheet as described in claim 1, characterized in that, The thickness of the spun sheet is 0.15mm to 0.3mm.
3. The high heat-shielding spun sheet as described in claim 1, characterized in that, The basis weight of the spun flakes is greater than 30 g / m 2 .
4. The high heat-shielding spun sheet as described in claim 1, characterized in that, The basis weight of the spun flakes is less than 120 g / m². 2 .
5. The high heat-shielding spun sheet as described in claim 1, characterized in that, The heat-blocking rate of spun yarn is 15% to 20%.
6. The high heat-shielding spun sheet as described in claim 1, characterized in that, The heat-blocking rate of spun yarn is 20% to 25%.
7. The high heat-shielding spun sheet as described in claim 1, characterized in that, The heat-blocking rate of spun yarn is 25%–30%.
8. The high heat-shielding spun sheet as described in claim 1, characterized in that, The attenuation rate ΔS of the heat-blocking efficiency of the spun yarn is 5% to 10%.
9. The high heat-shielding spun sheet as described in claim 1, characterized in that, The attenuation rate ΔS of the heat-blocking efficiency of the spun yarn is 10% to 15%.
10. A high heat-shielding spun sheet as described in claim 1, characterized in that, The longitudinal tensile strength (MTS) of the spun sheet is greater than 4.5 KN / m.
11. The high heat-shielding spun sheet as described in claim 1, characterized in that, The air resistance of the spun sheet is less than 35s.
Citation Information
Patent Citations
Polyethylene non-woven fabric and application thereof
CN114622341A
Multifunctional polymer non-woven fabric and fabric thereof
CN114687069A
Light and thin flash polymer non-woven fabric
CN114908478A
Flash fabric and application thereof
CN114990712A
Flash-spun sheet material
EP1213374A2